Analysis of State Court Of Batang Decision Number: 4 / Pid.Sus / 2018 / Pn Btg on Felony Obscenity Crime Based On Islamic Criminal Law - Bagus Langgeng Prasetiyo; Gunarto Gunarto; Munsharif Abdul Chalim (Jurnal Daulat Hukum, 2019)
In the case of sexual crimes where the child victim, the victim could be the driving factors behind crime. For example, we say today is increasingly widespread promiscuity, children have been left free in terms of promiscuity and lack of supervision of their parents, the They were released along with others, go anywhere. So, with their innocence, they could be trapped in one association and exploited by the parties or adults who are not responsible. In such circumstances, the public, law enforcement officers and even a State shall be estimated on the protection and supervision of children, especially where children as crime victims of sexual crimes indeed very concerned and could undermine future portion of the prospective successor to the nation.Therefore, the authors are interested in writing this thesis titled "Analysis of State Court of Batang Decision No. 4 / Pid.Sus / 2018 / PN Btg About felony obscenity According to Islamic Criminal Law".In this study the authors use this type of research descriptive with normative juridical approach. Data were collected by literature study, observation and interviews. Methods of qualitative analysis.At the end of the study authors conclude that the author found consideration of the judge in the imposition of a criminal judgment against the defendant in Decision No. 4 / Pid.Sus / 2018 / PN.Btg compliance, that have noticed the elements of the criminal case, after seeing the Islamic law according to the author was still lacking and not worth the Hadd punishment. So the result rather than the judge's decision according to the author can not be unfair to the accused and the victim.Keywords: Juridical Studies; Felony Obscenity Crime; Islamic Criminal Law